Dual-Network QSAZ@VPH hydrogel-mediated verapamil treatment improved recovery of diabetic ulcer through inhibiting mitochondrial oxidative stress and enhancing angiogenesis - Bin Chen; Hang Li; Yuliang Sun; Yuhua Li; Parisa Anvari; Ghazal Shokraneh; Menglin Cong; AmirMahdi Saeidi; Hecheng Ma; Tian Li; Gang Wang; Junhao Lin; et al. (Materials & Design)
Background: Diabetic ulcer (DU) are severe complications of diabetes, characterized by persistent inflammation, oxidative stress, and impaired mitochondrial function. Verapamil, a calcium channel blocker, has shown potential in reducing oxidative stress and improving mitochondrial dysfunction, but its application in DU treatment remains unexplored. Methods: A dual-network QSAZ@VPH hydrogel was developed for local delivery and controlled release of verapamil. In vitro experiments evaluated its protective effects on HUVECs exposed to H2O2-induced mitochondrial dysfunction, including inflammatory marker expression, apoptosis inhibition, and angiogenesis promotion. In vivo studies used db/db mice and DU model rats to assess wound healing, granulation tissue formation, and neovascularization. Results: In vitro, QSAZ@VPH reduced mitochondrial dysfunction, lowered inflammatory markers, inhibited apoptosis, and promoted angiogenesis. In vivo, the hydrogel significantly improved wound healing in both models, reversing impaired healing and promoting granulation tissue formation and enhanced neovascularization. Conclusions: The QSAZ@VPH hydrogel presents a promising strategy for diabetic ulcer therapy by targeting mitochondrial dysfunction and promoting tissue regeneration.